Resolution of Eosinophilic Peritonitis with Hypoalbuminemia by Oral Prednisone Acetate in an Elderly Patient Receiving Continuous Ambulatory Peritoneal Dialysis (Iranian Journal of Kidney Diseases, 2020)
A 79-year-old patient developed severe hypoalbuminemia associated with eosinophilic peritonitis (EP) after receiving continuous ambulatory peritoneal dialysis (CAPD) for 3 years. The hypoalbuminemia and EP treated successfully with the use of prednisone acetate. This case is reported to emphasize the importance of diagnosis of EP that should be suspected when the peritoneal dialysis (PD) patient presents with severe hypoalbuminemia combined with turbid effluent along with repeated negative cultures. A short course of low-dose oral glucocorticoid may be considered in accelerating the resolution of the episode in such cases.